1994
DOI: 10.1111/j.1399-3038.1994.tb00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary anti‐RSV IgA antibodies and respiratory infections during the first year of life in atopic and non‐atopic infants

Abstract: Salivary SIgA antibodies against RS virus were studied in 105 children during the first year of life. The infants were divided into groups according to their risk of atopy. At birth 13 neonates showed measurable amounts of SIgA to RS virus. In another 26 children specific antibodies were detected but in concentrations too low for quantitative analysis. During the first year of life this increased to 29 antibody-positive samples with measurable amounts of antibody and 39 with concentrations too low for quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(22 reference statements)
1
6
0
Order By: Relevance
“… 36 Several groups have looked at correlation between changes in salivary IgA and respiratory infections in individuals and found that decreases in IgA correlated with an increase in infections. These findings have been reported in a wide variety of subjects including from elite athletes, 37 infants, 38 healthy children 39 , 40 , 41 and children with Down’s syndrome. 42 These findings suggest that individuals that are muco-negative for salivary IgA against SARS-CoV-2 may be at an elevated risk for infection and/or disease severity.…”
Section: Discussionsupporting
confidence: 57%
“… 36 Several groups have looked at correlation between changes in salivary IgA and respiratory infections in individuals and found that decreases in IgA correlated with an increase in infections. These findings have been reported in a wide variety of subjects including from elite athletes, 37 infants, 38 healthy children 39 , 40 , 41 and children with Down’s syndrome. 42 These findings suggest that individuals that are muco-negative for salivary IgA against SARS-CoV-2 may be at an elevated risk for infection and/or disease severity.…”
Section: Discussionsupporting
confidence: 57%
“…It has been proposed that low levels of salivary IgA are associated with the development of allergy [9]. Decreased total IgA has already been described in the saliva of children with atopy [23] as well as defective salivary IgA responses against the respiratory syncytial virus were found in symptomatic allergic infants [24]. In another previous study, nonatopic healthy individuals had increased Der p1-specific IgA production in serum, but not for specific IgE antibodies [4].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of infants who develop severe RSV disease were born at term and are otherwise healthy. Among those, certain factors have been associated with severe disease: month of birth, age younger than 6 months, male sex, ethnicity [17], low socioeconomic status, crowded living conditions, number of siblings, indoor smoke pollution, day-care attendance [18], and a family history of asthma and atopy [19,20]. Many studies suggest that passively acquired maternal antibody confers protection against severe RSV disease [21,22], and incomplete transfer of maternally derived antibodies has been proposed as a contributing factor to the increased risk for RSV infection that is observed in preterm infants [9].…”
Section: Introductionmentioning
confidence: 99%